Początkowa wysokość świadczenia dla uczestników programu emerytalnego - Sipa, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article the methods of determining of the initial level of pension benefits are discussed. The first one is called the final pay principle, in which the initial level is calculated on the basis of the insurance seniority and the final pay. In the second method the accrual function is used. The pension in this case is considered as the accrued benefit of participant has acquired under the provisions of the plan. Furthermore, on the basis of the chosen methods of the calculations the value of the initial level of the pension benefit is presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 218-226